Continuous approximations of capacities on metric compacta - Hlushak, I.D.; Nykyforchyn, O.R. (Carpathian Mathematical Publications, 2016)
A method of "almost optimal" continuous approximation of capacities on a metric compactum with possibility measures, necessity measures, or with capacities on a closed subspace, is presented.